1996
DOI: 10.1152/ajpendo.1996.271.2.e232
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal tract protein synthesis and mRNA levels for proteolytic systems in adult fasted rats

Abstract: We studied protein turnover in the gastrointestinal tract of adult fasted rats, since the mechanisms responsible for protein wasting in these tissues are poorly understood. Protein mass of stomach, small intestine, and colon decreased by 14-29 and 21-49% after 1 and 5 days of fasting, respectively. The fractional rate of in vivo protein synthesis (ks) was approximately 34% lower in the stomach after 1 and 5 days of fasting due to decreased capacity for protein synthesis (Cs). In small intestine and colon, ks w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 16 publications
3
28
1
Order By: Relevance
“…In organs such as the liver and the muscle, protein degradation results from the activity of the three major systems: the lysosomal (cathepsins), the Ca 2þ -activated (calpains), and the ATP-ubiquitindependent proteolytic pathways (Samuels et al, 1996) These pathways have also been reported to occur in rat intestinal mucosa. Enteral glutamine stimulates mucosal protein synthesis and attenuates ubiquitindependent proteolysis improving protein balance in human gut.…”
Section: Protein Synthesis and Degradationmentioning
confidence: 99%
“…In organs such as the liver and the muscle, protein degradation results from the activity of the three major systems: the lysosomal (cathepsins), the Ca 2þ -activated (calpains), and the ATP-ubiquitindependent proteolytic pathways (Samuels et al, 1996) These pathways have also been reported to occur in rat intestinal mucosa. Enteral glutamine stimulates mucosal protein synthesis and attenuates ubiquitindependent proteolysis improving protein balance in human gut.…”
Section: Protein Synthesis and Degradationmentioning
confidence: 99%
“…Fasting has also been shown to affect rates of protein synthesis in the gut of some animals (McNurlan et al, 1979;Kelly et al, 1993;Samuels et al, 1996). In the intestine of many animals protein biosynthesis can account for up to 30% of the rate of oxygen consumption of the tissue (McBride and Kelly, 1990) and thus is a likely target for suppression especially in metabolically depressed organisms.…”
Section: Energy Costs Of the Si During Aestivationmentioning
confidence: 99%
“…In main organs such as the liver and the muscle, the degradation of proteins results from the activity of the three major systems, the lysosomal (cathepsins), the Ca 2ϩ -activated (calpains), and the ATP-ubiquitin-dependent proteolytic pathways. These pathways have been reported in rat intestinal mucosa (35), but data in human mucosa are still limited. The aim of this study was to investigate the effects of enteral glutamine on gut mucosal protein synthesis and on the mRNA levels for the main proteolytic systems in healthy volunteers.…”
mentioning
confidence: 90%
“…This last pathway is believed to be the most important one (39). In the gastrointestinal tract, little information is available, although all three processes have been identified in the small intestine of the rat (19,35). The expression of the components of proteolytic pathways was increased during fasting in rats (35) but not during short-term underfeeding in ewes (30).…”
mentioning
confidence: 99%